(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The essay is focused on a specific component of the Italian solidarity toward the victims of Latin American military coups: women’s association, as widely known, a plural world. Based on primary sources, it considers the time span included between the first episode of that kind – the Brazilian coup of 1964 – and Chile’s 1973 one, an experience that produced a widespread and constant interaction between civil society and political institutions in our country. Through fund raising, counter information and multiple forms of denounce, several female associations in Italy have made their voice heard in support of the victims – women themselves – of political repression in Latin America during the ‘long seventies’. It was a decade in which, along with women’s enhanced participation in the public sphere, transnational activism began to denounce authoritarian regimes’ human rights abuses.